Characterization of protein therapeutics using mass spectrometry (Springer US Imprint: Springer, 2013)
Protein therapeutics' high efficacy, safety, and ability to treat life-threatening diseases such as cancer, inflammation and genetic disorders have revolutionized modern medicine. In 2012, 200 companies competed in this $90 billion year industry.   In Characterization of Protein Therapeutics using Mass Spectrometry, expert contributors from academia and industry highlight current approaches and future trends. The book discusses mass spectrometry techniques as related to the analysis of protein therapeutics, structural identification strategies and quantitative approaches. The book also covers various studies involving characterization of process related protein drug impurities/degradants, metabolites, PTMs and  higher order structures of protein therapeutics.   General practitioners in pharmaceutical research, specialists in analytical sciences, and graduate students studying mass spectrometry and pharmaceutical sciences will find this book useful because of  the  step-by-step approaches and new strategies to solve challenging problems related to protein therapeutics research and development.